Exploration of the Improvement of Shape Memory Alloys for Elastocaloric Refrigeration - Luo, Qiyuan (Transactions on Environment, Energy and Earth Sciences, 2026)
Elastomeric cooling, an emerging solid-state cooling technology that uses the reversible phase transition between austenite and martensite in shape memory alloys (SMA) under stress for cooling, has advantages such as high COP and environmental friendliness, and is expected to replace traditional cooling methods. This paper systematically presents the basic principles of elastocaloric refrigeration, the methods for characterizing material properties and the progress of equipment research. The fatigue life, elastocaloric effect and cooling efficiency of SMA were significantly enhanced through material modification (such as element doping, concentration gradient design, and nanocrystalline structure regulation) and structural optimization (such as thin-walled tubes, thin-film multilayer coupling, tilt, and roller drive design). Despite the current challenges of fatigue life, equipment compactness and energy utilization efficiency, elastomeric cooling technology shows broad application prospects in low-carbon environmental protection and efficient cooling. Although it still faces challenges such as fatigue life, equipment compactness and energy utilization efficiency at present, elastomer cooling technology shows broad application prospects in the fields of low-carbon environmental protection and efficient refrigeration.